MOTIVASI KERJA PADA GURU HONORER DI INDONESIA: A LITERATURE REVIEW - Rifda Alda Ufaira; Wiwin Hendriani (State Islamic University (UIN) Ar-Raniry, 2019)
The topic of honorary teachers is a limited topic because it only occurs in Indonesia. Then, there is not much research on work motivation for honorary teachers. Therefore, this literature research aims to discuss further about several studies that related to work motivation in the honorary teachers. Literature search was carried out on the Portal Garuda Google databases, specifically in Jakarta State University journal collection from 2014 to the present. There are 3 research journal articles that have been identified using inclusive and exclusive criteria. Based on the review that has been done, there are several things that affect work motivation, including quality of work life and professional competence. Work motivation can also have an impact on other things, such as the performance of honorary teachers themselves. And if work motivation coupled with job satisfaction, that will affect the productivity and effectiveness of honorary teachers.